Elusive Diagnosis of Superﬁcial Peroneal Nerve Entrapment Case report - R. Rapčan; L. Kočan; H. Alfredson; R. Sudzina; S. Rapčanová; M. Buriánek; P. Török (Общая реаниматология)
Isolated neuropathy of the superﬁcial peroneal nerve (SPN) is a relatively rare type of peripheral neuropathy. It is linked to the mechanical entrapment of the SPN in predisposed locations of its anatomical pathway. Associated clinical ﬁndings are insuﬃcient lifting of the latero-dorsal part of the foot, stepping on the lateral border of the foot, and commonly, a strong pain localized in the nerve dermatome.Case report. We describe a case of a 14-year-old female patient with right leg pain lasting 24 months. Repeated neurological examinations with negative ﬁndings on electromyography (EMG) were performed. The patient underwent a Steindler surgery for a suspected diagnosis of a heel spur, without any improvement. Despite complex pharmacotherapy, chronic pain developed. The patient was unable to walk, being bound to a wheelchair. Amputation of her lower limb under the knee was also considered. SPN entrapment was diagnosed at a physical examination at EuroPainClinics. Decompression of the SPN under local anaesthesia was performed at the clinic.Results. The symptoms improved immediately after the procedure, and following 2 months of rehabilitation, the patient was completely symptom-free. Her clinical state remains unchanged until this day.Conclusions. SPN entrapment is not a common diagnosis in the group of pain syndromes. Regarding the lower limb, it is imperative to include it on the list of diﬀerential diagnoses in cases of pain and functional disorders of the lateral muscle groups of the calf and leg. In the case of SPN entrapment, EMG ﬁndings may be negative.